2022
DOI: 10.19184/stoma.v19i1.30700
|View full text |Cite
|
Sign up to set email alerts
|

Profil Kesehatan Gigi dan Mulut Berdasarkan Standar WHO pada Masyarakat Kecamatan Kaliwates Kabupaten Jember

Abstract: Indonesia's oral and dental health problems are quite high, including in Kaliwates Subdistrict. The newest method for looking at oral and dental health conditions operates WHO standard dental and oral health forms. Oral health data can be used as preventive, curative, and rehabilitative measures. The aim of this study was to determine oral health profile based on WHO standards in Kaliwates Subdistrict, Jember Regency. The research conducted was a descriptive observational with the cross-sectional approach by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Most people still left their cavities untreated, resulting in more severe tooth decay. 8 Dental caries with a very high category was the most common in the community. The results of this study are in line with research conducted by Amelinda et al (2022) which found that the dental caries in Kaliwates District, Jember Regency is in a very high category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most people still left their cavities untreated, resulting in more severe tooth decay. 8 Dental caries with a very high category was the most common in the community. The results of this study are in line with research conducted by Amelinda et al (2022) which found that the dental caries in Kaliwates District, Jember Regency is in a very high category.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are in line with research conducted by Amelinda et al (2022) which found that the dental caries in Kaliwates District, Jember Regency is in a very high category. 8 The problem of the high level of caries experienced by the community could be caused by several internal factors and external factors including diet and tooth brushing behavior. Types of foods that have an impact on the process of forming dental caries are cariogenic foods that contain sweet and sticky carbohydrates such as candy, chocolate, biscuits, ice cream, and other sweet foods.…”
Section: Discussionmentioning
confidence: 99%
“…Dental and oral health is an indicator of overall health, well-being and quality of life (Amelinda, et al, 2022). However, dental and oral health problems are still experienced by many countries, both developed and developing countries, which still receive little attention and even tend to be ignored.…”
Section: Introductionmentioning
confidence: 99%